Community Cultural Development for Social Change: Developing Critical Praxis - Christopher C. Sonn; Amy F. Quayle (Journal for Social Action in Counseling and Psychology, 2014)
A growing number of writers in community psychology have called for re-claiming the radical impetus that inspired the development of the field. In this article we describe a program of work facilitated by a community cultural development agency that uses community arts practice to create, promote and improve opportunities for participation, network development, and empowerment in rural Western Australian communities. The program of work we describe in this article sits within a broader systematic effort aimed at social change in a specific geographic region of Western Australia, and reflects a particular commitment to challenging the continuing social exclusion of Aboriginal people in postcolonizing Australia. Informed by writing within community and liberation psychologies, we discuss three community arts projects and highlight the key concepts of participation, power/empowerment and situated knowing in our examination of community cultural development as participatory methodology. We emphasize the iterative and generative nature of arts practice and argue that community cultural development practice is often aimed at both instrumental as well as transformative outcomes. We suggest that the transformative dimensions require a critical theoretical lens to help explicate the operations of power and coloniality in the micro settings of community practice.